Curcumin combined with metformin decreases glycemia and dyslipidemia, and increases paraoxonase activity in diabetic rats - Roxo, Daniela Fernandes [UNESP]; Arcaro, Carlos Alberto [UNESP]; Gutierres, Vania Ortega [UNESP]; Costa, Mariana Campos [UNESP]; Oliveira, Juliana Oriel [UNESP]; Lima, Tayra Ferreira Oliveira [UNESP]; Assis, Renata Pires [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Baviera, Amanda Martins [UNESP] (Springer Nature, 2019)
Background: Combination of current antidiabetic agents with natural antioxidants to manage diabetes mellitus and its complications has appeared as an emerging trend. Curcumin, a yellow pigment isolated from Curcuma longa rhizomes, has gained attention due to its beneficial effects in controlling the disturbances observed in diabetes mellitus. The purpose of this study was to investigate if yoghurt enriched with curcumin and metformin, individually or as mixtures, ameliorates physiometabolic parameters, glycoxidative stress biomarkers, and paraoxonase 1 (PON 1) activity in diabetic rats. Methods: Streptozotocin-diabetic rats (6-week-old Wistar rats) were treated for 30 days with curcumin and metformin, isolated or as mixtures in yoghurt (10 rats/group). After treatments, the plasma levels of glucose, triacylglycerol, cholesterol, thiobarbituric acid reactive substances (TBARS, a biomarker of lipid oxidation), fluorescent advanced glycation end products (AGEs), and the activity of PON 1, an antioxidant enzyme were assessed. Data were analyzed using one-way analysis of variance (ANOVA) followed by Student-Newman-Keuls test. Results: Treatment of diabetic rats with curcumin or metformin alone decreased the plasma levels of glucose, triacylglycerol, cholesterol, TBARS, and fluorescent AGEs, as well as increased the activity of PON 1. The combination of metformin with curcumin further decreased dyslipidemia and TBARS levels in diabetic rats, indicating synergy, and maintained the high levels of PON 1. Conclusion: These findings indicated that curcumin combined with metformin may act synergistically on dyslipidemia and oxidative stress, as well as increased PON 1 levels. Therefore, it might be a promising strategy for combating diabetic complications, mainly the cardiovascular events.
Keywords: Curcumin; Diabetes mellitus; Glycoxidative stress; Paraoxonase